EXHAUST ANALYSIS AND PERFORMANCE OF A SINGLE CYLINDER DIESEL ENGINE RUN ON DUAL FUELS MODE (Journal of Engineering, 2011)
Generally fossil based fuels are used in internal combustion engines as an energy source.Excessive use of fossil based fuels diminishes present reserves and increases the air pollution inurban areas. This enhances the importance of the effective use of present reserves and/or to developnew alternative fuels, which are environment friendly. Use of alternative fuel is a way of emissioncontrol. The term “Alternative Gaseous Fuels” relates to a wide range of fuels that are in thegaseous state at ambient conditions, whether when used on their own or as components of mixtureswith other fuels.In this study, a single cylinder diesel engine was modified to use LPG in dual fuel mode to studythe performance, emission, and combustion characteristics. The primary fuel, liquefied petroleumgas (LPG), was mixed with air, compressed, and ignited by a small pilot spray of diesel. Dual fuelengine showed a reduction in oxides of nitrogen in the entire load range. The brake thermalefficiency improved by 3% in dual fuel mode, especially at low load, and also reduced thehydrocarbon, carbon monoxide, and CO2 emissions.